Glucose Levels and Bacteria Identification in Cantang Groupers Distributed from Hatchery Bali - Lilis Cahaya Septiana; Gunanti Mahasri; Ahmad Shofy Mubarak; Ika Putri, Lia Oktavia (Grouper, 2025)
Cantang grouper is a hybridization between female tiger grouper and male kertang grouper. Transporting fish using a closed transportation system can cause stress, which results in increased blood glucose levels in fish as a secondary physiological response. This study aims to analyze blood glucose levels and identify bacteria in cantang grouper (Epinephelus fuscoguttatus lanceolatus) distributed from hatcheries in Bali. The results showed that the average blood glucose level reached 102 mg/dL, higher than the normal range (27–56 mg/dL), indicating that the fish experienced stress due to bacterial infection and the transportation process. The cantang grouper observed had been infected with Vibrio alginoliticus bacteria with the lowest TVC value of 98 x 105 CFU/mL and the highest 239 x 105 CFU /mL. The relationship between blood glucose and TVC values is positively correlated. The higher the blood glucose, the higher the TVC value in cantang grouper. Bacterial identification revealed the presence of Vibrio alginolyticus, a major pathogen causing vibriosis in marine fish. This study highlights the importance of improving transportation systems and implementing strict biosecurity to reduce stress and infection in cantang grouper